Factors Associated with the Incidence of Dengue Hemorrhagic Fever (DHF) at the Suruh Trenggalek Health Center - Tri Adi Putra; Agusta Dian Ellina (Open Access Health Scientific Journal, 2020)
Background: Dengue Hemorrhagic Fever (DHF) is one of the public health problems in Indonesia which tends to increase in the number of patients and the wider its spread. The purpose of this study was to determine the factors for the occurrence of Dengue Hemorrhagic Fever (DHF) in the Public Health Center in Suruh Trenggalek. Method: The research design used is quantitative with a "cross sectional" approach. The sampling technique used is Simple Random Sampling with a sample of 108 respondents. Data analysis technique using Logistic Regression. Results: The results showed that there was a relationship between the habit of hanging clothes with the incidence of dengue hemorrhagic fever, with a p-value of 0.000 < = 0.05. The results showed that there was a relationship between the frequency of bathtub draining and the incidence of dengue hemorrhagic fever, with a p-value of 0.000 < = 0.05. The results showed that there was a relationship between the presence of larvae with a p-value of 0.000 < = 0.05. Simultaneous test results also show the influence of all variables on the incidence of dengue hemorrhagic fever with a p-value of 0.000 < = 0.05. Conclusion: It is hoped that there will be cooperation between local village government health officers and the community in order to minimize the incidence of dengue hemorrhagic fever